Penerapan Online Single Submission Dalam Pelayanan Perizinan UMKM Di Desa Ambulu Kecamatan Sumberasih Kabupaten Probolinggo - Yoseph Santovino Roso; Amisha Novita Arif; Tesa Putri Rivayanti; Ersa Falevi Anggraini; Kalvin Edo Wahyudi (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Researchers focused on the implementation of OSS (Online Single Submission) system in managing Micro Small and Medium Enterprises (MSMEs) in Ambulu Village, Sumberasih District, Probolinggo Regency, seeing that there are still business actors in those area who do not yet have license to do business. This research or study aims to identify and analyze the implementation of Online Single Submissio in facilitating services for making business licenses for MSMEs in Ambulu Village, Sumberasih District, Probolinggo Regency. The research method used is qualitative descriptive method. Data collection techniques in research are interviews, and observation techniques. Based on researched, business licensing service on Ambulu Village already running well but, there are still problem faced, namely that there are still some business actors who lack information regarding the business licensing process.